Serum Lipid Profile İn Children with Thalassemia Major: A Study On 184 Cases - TERZİ, ÖZLEM (Clinical Medicine And Health Research Journal, 2023)
Background: Patients with thalassemia major are at risk of developing abnormal lipid profiles. Aim: In this study, the relationship between iron accumulation and blood lipid profile in TM children was evaluated. Methods: In this study, blood hemoglobin, ferritin, and lipid levels of pediatric patients with TM aged 1-18 years were investigated. Those with other chronic diseases were excluded from the study. Results: The median age of 184 patients included in the study was 8 (range 1-18), and 96 (52.2%) of the patients were girls. There is an inverse and statistically significant relationship between age and total cholesterol (TC) level (p<0.05) and age and low-density lipoprotein cholesterol (LDL-C) level (p<0.05). There was an inverse, and statistically significant correlation between ferritin- high-density lipoprotein cholesterol (HDL-C) levels (p:0.015). Conclusion: As ferritin levels increase in children with thalassemia, HDL-C levels decrease. For cardiac iron accumulation, HDL-C level may be a guide instead of ferritin.